The role of antibodies in enzyme treatments and therapeutic strategies. Issue 2 (March 2015) - Bigger, Brian W.; Saif, Muhammad; Linthorst, Gabor E.
Abstract : Substitution of the defective lysosomal enzyme in lysosomal storage disorders (LSDs) often elicits antibody formation towards the infused protein. Aside from Gaucher disease, antibodies often lead to infusion associated reactions and a reduced biochemical response. In Pompe disease, antibody titer is predictive of clinical outcome, but this is less apparent in other LSDs and warrants further study. Few laboratories are capable of enzyme-antibody determination: often physicians need to rely on the enzyme manufacturer for analysis. Currently, laboratories employ different antibody assays which hamper comparisons between cohorts or treatment regimens. Assay standardisation, including measurement of antibody-related enzyme inhibition, is therefore urgently needed. Successful immunomodulation has been reported in Pompe and in Gaucher disease, with variable success. Immunomodulation regimens that contain temporary depletion of B-cells (anti-CD20) are most used. Bone marrow transplantation in MPS-I results in disappearance of antibodies. No other clinical studies have been conducted in humans with immunomodulation in other LSDs.